Organotypic models of type III interferon-mediated protection from Zika virus infections at the maternal–fetal interface - Corry, Jacqueline (Proc Natl Acad Sci U S A, 2017)
Protecting the fetus from the hematogenous spread of viruses requires multifaceted layers of protection and relies heavily on trophoblasts, the fetal-derived cells that comprise the placental barrier. We showed previously that trophoblasts isolated from full-term placentas resist infection by diverse viruses, including Zika virus (ZIKV), and transfer this resistance to nonplacental cells through the activity of paracrine effectors, including the constitutive release of type III interferons (IFNs). Here, we developed 3D cell-line–based models of human syncytiotrophoblasts, cells that lie in direct contact with maternal blood, and show that these cells recapitulate the antiviral properties of primary trophoblasts through the constitutive release of type III IFNs (IFNλ1 and IFNλ2) and become resistant to ZIKV infection. In addition, using organotypic human midgestation chorionic villous explants, we show that syncytiotrophoblasts isolated from the second trimester of pregnancy also constitutively release type III IFNs and use these IFNs in autocrine and paracrine manners to restrict ZIKV infection. Collectively, these data provide important insights into the defense mechanisms used by syncytiotrophoblasts at various stages of human gestation to resist ZIKV infection and new human models to study the role of type III IFNs in the vertical transmission of ZIKV and other viruses associated with congenital disease.